Women in antiquity: real women across the ancient world - Budin, Stephanie Lynn; Turfa, Jean MacIntosh (Rewriting antiquity, 2016)
Women in Antiquity- Front Cover -- Women in Antiquity -- Title Page -- Copyright Page -- Contents -- List of illustrations -- Figures -- Tables -- Maps -- List of abbreviations -- Notes on contributors -- General introduction -- Chronological designations -- Note -- PART I: Mesopotamia -- Chronology -- Introduction -- Suggested further reading -- Chapter 1: Female sexuality in Mesopotamia -- Sources -- Terminology -- Sexual desire -- Types of sex -- Helping the menfolk get it up -- Sex and the law -- The Ḫarimtu question -- The erotic Ḫarimtu -- The practical Ḫarimtu -- Notes -- References